Phylogeny of Salmonidae Family Inffered from D-loop Mitochondrial Marker - Miad Khalaf; Gina Oana Popa; Sergiu Emil Georgescu; Andreea Dudu; Marieta Costache (Scientific Papers Animal Science and Biotechnologies, 2023)
Salmonids are a heterogeneous group of fish classified in one family – Salmonidae. These species are natives of the northern hemisphere, but currently have been introduced in many countries all over the world for sport fishing and aquaculture. Despite the considerable importance of salmonids, their evolutive history is still a controversial issue.